Strategi Pemasaran Produk Murabahah Di Koperasi Serba Usaha Baitul Maal Wattamwil Marhaban Rembang Purbalingga - Frefitasari, Hety (2016)
The purpose of this study is to describe the product marketing strategy of Murabahah conducted by KSU BMT Marhaban Purbalingga Rembang. The method used in this research is qualitative method with descriptive approach. This study was conducted in Rembang Marhaban KSU BMT Purbalingga, research carried out for six months, since September 2015 until the month of December 2015. Sources of data used primary data and secondary data obtained through interviews and observations. Informant in this research is the Manager, Marketing and Customer service. Validity of the data using triangulation methods and triangulation of sources. Data analysis technique using an interactive model that consists of data reduction, data presentation and conclusion. Results of this research is the marketing strategy of Murabahah products using the marketing mix (marketing mix) with a model of seven components: 1) Product (product) that is marketed consists of various kinds, there is a fund products and financing products. For products there are product financing Mudaraba financing, Musharaka and Murabaha, but the most in demand by the public is Murabaha financing products. 2) Price (price) are applied, namely by taking profits in accordance with the agreement between BMT and party members. 3) location (place) which is strategically located in the BMT edge of the highway so it is easy to reach by public transport. 4) Promotion (promotion) is applied which is more emphasis on kinship systems and a personalized approach, and information by word of mouth. 5) The person (people), the strategies are giving priority to service excellence and professional. 6) Physical evidence (physical evidence), a performance that seeks to provide satisfaction to the members with optimal service. 7) Process (proses) in the delivery of services refers to the SOP and to provide funding application procedures that are standard requirements, quickly and safely in order to attract members.